Atrial size and function in athletes - Gjerdalen, G. F.; Hisdal, J.; Solberg, E. E.; Andersen, T. E.; Radunovic, Z.; Steine, K. (International Journal of Sports Medicine, 2015)
We wanted to explore whether change in LA (left atrium) size would influence LA function, or increase regurgitation in the atrioventricular valves. 595 male elite football players and 47 non-athletic controls were included. End-systolic LA volume and RA area and end-diastolic LV volume and RV area were measured by 2-dimensional (2D) echocardiography Pulsed and colour Doppler were used to estimate tricuspid and mitral regurgitations. 2D longitudinal strain of the 50 football players with the largest LA volumes were compared with the 50 players with the smallest LA volumes. The LA volumes in some athletes with large atria were more than tripled, compared to athletes with small atria. 2D strain however, could not reveal any impairment of LA function in the players with the largest atria, compared to those with the smallest LA. Tricuspid valve regurgitation was found in 343 (58%) of the athletes, compared to 17 (36%) of the controls (p<0.01), while mitral regurgitation was found in 116 (20%) football players and 7 (15%) controls (NS). Furthermore, the RA area was significantly larger in athletes with tricuspid regurgitation compared to athletes without. The present study demonstrated a huge variation in atrial size between the athletes. This variation, however, had no impact on LA function. Tricuspid regurgitation was significantly more prevalent among the athletes, than among the controls.